Misdirection due to early magnetoencephalographic presentation and management in Rasmussen encephalitis: a case report - Han, Jinkun; Fan, Xiaotong; Chen, Sichang (Frontiers in Neurology, 2023)
Rasmussen encephalitis is a rare and unexplained chronic brain hemispheric inflammatory disease. We report a case of epilepsy in which magnetoencephalography showed dipoles localized only in the operculum. Because the patient’s clinical presentation and examination findings did not meet the diagnostic criteria for Rasmussen encephalitis, he underwent cortical electroencephalogram (ECoG) record and limited resection surgery. However, the seizures were not relieved after surgery, and imaging findings showed significant features of hemisphere atrophy. This young male patient was eventually diagnosed with Rasmussen encephalitis and the seizures was completely vanished following hemispherectomy. His data can provide a reference for the early identification of this devastating disease.